Characterisation of novel Claudin gene expression during Petromyzon marinus embryo development - Dean, Nicholas (My University, 2015)
Claudins are a family of proteins that are conserved amongst all vertebrates, they are integral in the formation and maintenance of the tight junctions between epithelial cells. Claudins are implicated in embryo morphogenesis, vertebrate evolution, solute movement, cell-cell adhesion, designation of cellular and tissue identity, and several diseases when mutated. Petromyzon marinus (the sea lamprey) is the most basal extant vertebrate and is a model organism in both developmental and evolutionary biology for this reason. In this study, the expression patterns and functions of novel claudin genes in P. marinus were examined with the aim of discovering more about the role of claudins in vertebrate evolution. Presumptive claudin genes in P. marinus were compared to all known claudins in the NCBI database. Primers were designed against all known P. marinus claudin genes and RT-PCR was performed in order to determine their expression levels at embryonic stages E8 to E18, as well as in adult eye, gill, heart, liver and skin tissues. Probes were designed against Claudin 1a, Claudin 9, Claudin 10 and Claudin 19b and RNA in situ hybridisation was performed on embryos at developmental stages E4 to E31 in order to determine their spatial expression patterns. Areas of common claudin gene expression appear to include the pharyngeal arches, otic placode, neural tube, notochord and ectoderm. Claudin 1a is uniquely expressed in the lamprey migrating neural crest. Morpholino-mediated gene knockouts were performed on P. marinus embryos and the loss of Claudin 19b appears to result in abnormal somite morphogenesis.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2015.
Keywords: Sea lamprey.; Gene expression.; Embryology.